Assessment of crop-raiding along the buffer zone of oba hills national park, Nigeria (2021)
The Conservation and sustainable use of a natural protected area require concerted efforts of conservation managers and the local communities. Crop raiding is a major problem confronting conservationists and communities around the park area. This paper examines crop damage by mammals and birds, the farmers' experiences on crop losses along the park boundary. Data were collected via weekly counts of damaged crops in twenty (20) farmlands in the wet season and thirtythree (33) farmlands in the dry season. The study was conducted in Oba Hills National Park located in Iwo, Iwo Local Government Area of Osun State, Nigeria. A reconnaissance survey (on foot) of the park was carried out to be conversant with the park. One hundred (100) questionnaires were administered to the respondents in six selected communities due to their proximity to the park. Data were analyzed descriptively using the percentage frequency distribution test. Analyses show that the majority (67%) of the respondents at the park boundary are male. Ninety-five percentages (95%) of the damages observed were perpetrated by the wild animals on annual crops. Correlation analysis shows no significant relationship between the farmer's socio-economic characteristics and measures employed to combat and repel marauding wild animals. The study reveals that (82%) of the respondents were on the commercial farming system while (18%) of them were on subsistence farming. The crops of the respondents suffer invasion by wild animals especially the monkeys, throughout the year. On average, farmers record a loss of Three hundred thousand naira (approx. $600) as a result of farm invasion. Management of crop-raiding, in general, requires an integrated approach involving both the park staff and surrounding communities. This synergy will be surely minimized if not eliminate conflicts arising from crop-raiding by wild animals.